Oḍiā sāhityare tribeṇī yuga - Dāśa Mahāpātra, Yadunātha, 1929- (Nālanda, 1980)
Study on the lives and works of Fikir Mohan Senapati, 1843-1918, Radhanath Roy, 1848-1908, and Madhusudan Rao, 1853-1912, Oriya litterateurs and their influence on contemporary literature.